2015
DOI: 10.1111/jeb.12544
|View full text |Cite
|
Sign up to set email alerts
|

Floral isolation is the major reproductive barrier between a pair of rewarding orchid sister species

Abstract: The crucial role of reproductive isolation in speciation has long been recognized; however, a limited number of studies quantify different isolation barriers and embed reproductive isolation in a phylogenetic context. In this study, we investigate reproductive isolation between the often sympatrically occurring orchid species, Gymnadenia conopsea and G. odoratissima. We examine the phylogenetic relationship between the two species and analyse floral isolation, fruit set and seed viability from interspecies cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 62 publications
3
38
0
1
Order By: Relevance
“…Therefore, the most important drivers of orchid speciation are likely to be both spatially linked and biotic. A critical factor is likely to be insect diversity; switching to a new pollinator species is instrumental in orchid speciation (Breitkopf, Onstein, Cafasso, Schlüter, & Cozzolino, ; Peakall & Whitehead, ; Peter & Johnson, ; Sun, Schlüter, Gross, & Schiestl, ). Mycorrhizal fungi diversity is less important than pollinators in orchid speciation (Phillips et al, ), but mycorrhizae do nonetheless determine the subset of sites that an orchid can colonize within its possible climatic range (McCormick & Jacquemyn, ; Nurfadilah et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the most important drivers of orchid speciation are likely to be both spatially linked and biotic. A critical factor is likely to be insect diversity; switching to a new pollinator species is instrumental in orchid speciation (Breitkopf, Onstein, Cafasso, Schlüter, & Cozzolino, ; Peakall & Whitehead, ; Peter & Johnson, ; Sun, Schlüter, Gross, & Schiestl, ). Mycorrhizal fungi diversity is less important than pollinators in orchid speciation (Phillips et al, ), but mycorrhizae do nonetheless determine the subset of sites that an orchid can colonize within its possible climatic range (McCormick & Jacquemyn, ; Nurfadilah et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among-population variation in interactions with pollinators may result in divergent selection on floral traits, promoting floral diversification (Grant, 1949(Grant, , 1994Stebbins, 1970;Van der Niet & Johnson, 2012; Van der Niet, Peakall, & Johnson, 2014), and the formation of pollination ecotypes (Anderson, Alexandersson, & Johnson, 2010;Johnson, 1997;Van der Niet, Pirie, Shuttleworth, Johnson, & Midgley, 2014). However, ecotypes (e.g., Armbruster, 1985;Boberg et al, 2014;Van der Niet, Pirie, et al, 2014) and closely related species (e.g., Campbell, Waser, & Melendez-Ackerman, 1997;Sun, Schlüter, Gross, & Schiestl, 2015) commonly differ in multiple traits that can be strongly correlated within and across populations, and the relative contribution of different traits to adaptive differentiation is usually poorly known. Because of strong trait correlations, experimental approaches are required to determine the independent and combined effects of individual traits on pollination success and plant fitness (Campbell, 2009;Castellanos, Wilson, & Thomson, 2004;Schemske & Bradshaw, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…left aside because it has been suggested that the (relative) amount of scent compounds is highly affected by environmental (nongenetic) effects and is relatively evolutionarily labile (e.g., highly adaptive) to be used in phylogenetic studies (Barkman 2001;Levin et al 2003). Indeed, floral scents can be different between closely related species, not only through particular ratios of more widespread compounds, but also through specific key compounds (Schiestl and Ayasse 2002;Raguso 2008;Waelti et al 2008;Ayasse et al 2011;Okamoto et al 2015;Sun et al 2015). Moreover, both specific key compounds and a specific ratio of (common) compounds may be exposed to phenotypic selection (Andersson 2003;Galen et al 2011;Schiestl et al 2011;Parachnowitsch et al 2012).…”
Section: Introductionmentioning
confidence: 99%